'Mon petit essai': Émilie du Châtelet's Essai sur l'optique and her early natural philosophy. Issue 4 (4th July 2019) - Gessell, Bryce
ABSTRACT: Émilie du Châtelet's recently-discovered Essai sur l'optique offers new insights into her early natural philosophy. Here I analyse the Essai in detail, focusing on Du Châtelet's use of attraction and her discussion of the laws governing it. These features of the Essai are crucial to her early thought. I also analyse how other contemporaneous sources augment the Essai, including her review of Voltaire's Elémens and her correspondence with Maupertuis. These sources track her growing appreciation of the need for a metaphysical framework in science. I also discuss the Essai 's implications for key passages of the Institutions de physique .